Food upcycling focusing on private households: the potential of food upcycling in rural areas - Schulte, Henning; Stelloh, Tadea Danuta; Schleyerbach, Urte; Bornkessel, Sabine (Frontiers in Sustainable Food Systems, 2025)
IntroductionGiven the increasing importance of sustainability and the high levels of food waste, this descriptive, quantitative study explored food upcycling as a potential strategy to reduce waste, focusing on rural households in Germany.MethodsA survey of 228 participants (response rate of 66%) examined the acceptance of food upcycling practices for fruits and vegetables in different age groups.ResultsWhile awareness of food waste is high, practical engagement with food upcycling remains limited. Notably, 51% of respondents was unfamiliar with the term “food upcycling,” although some of them may already be unknowingly apply this practice. Only 6% reported frequent upcycling of fruits and vegetables, while 59 % never do so.DiscussionGenerational trends suggest that older consumers (baby boomers and the post-war generation) are more likely to engage in food upcycling and show greater willingness to adopt and promote it. Younger generations (Gen Z and Gen Y), despite higher familiarity with the term, exhibit more neutral behavior and lower commitment. The results highlight a need for targeted initiatives to bridge the gap between knowledge and practice, especially in rural areas. Future research should include urban comparisons and a greater focus on inter-generational differences to encourage and support broader adoption of sustainable practices like food upcycling.